Pathogens from fomites in clinical setting: a scoping review - Muhammad, Izzati; Wan Ismail, Wan Nur Izzati; Samsuddin, Niza; Alias, Norsyuhada (IIUM Press, 2023)
Fomites can potentially transmit infectious or contagious pathogens thus contribute to the widespread of hospital-associated infections (HAIs). A scoping review was conducted to identify the types of fomites and pathogens as well as factors of pathogen distribution in clinical setting according to Arksey & O’Malley framework and PRISMA-ScR guidelines. Three online databases were used to collect the relevant data which revealed that there were 46 reported fomites in clinical setting that have been associated with bacteria, virus, and fungi. The most contaminated fomite with more than 10 species of pathogens was the mobile phone. This distribution might be due to the attitudes of healthcare workers and patients and their practice towards cleaning of mobile phones that prominent especially in Intensive Care Units (ICUs). Future study could investigate the effectiveness of proper hygiene to evaluate the contribution of this action towards the reduction of fomites contamination in the hospital.